Pelatihan Marketing Pengembangan Kelompok Ekonomi Produktif Desa Prima RAHAYU PRIMA - Noviadry Nur Tamtama; Choiril Hana Mustofa (Universitas Muhammadiyah Klaten, 2023)
Indonesia, with a population of more than 270 million people and potential natural resources and human resources, has great power to grow in terms of the economy. Micro, Small and Medium Enterprises are one of the mainstays of Indonesia's economic growth in realizing the welfare of society at large. Prima Village or known as the Prima Productive Economic Group is a women's empowerment program in the Special Region Province of Yogyakarta under the responsibility of the Women's Empowerment Service, Child Protection and Population Control, Special Region Province of Yogyakarta. Empowerment is carried out through coaching to open small businesses and strengthening existing small and medium businesses in all districts and cities in Special Region Province of Yogyakarta. Productive Economic Group Desa Prima in Sumberrahayu Village, Moyudan District, Sleman Regency is one of the many Productive Economic Groups in Special Region Province of Yogyakarta that requires further steps so that established businesses have advantages and the ability to compete with existing products or services on the market. The program needed is to provide insight and provision in marketing products and services for Micro, Small and Medium Enterprises players who are members of it. The aim of this service activity is to provide understanding and marketing strategies in the Prima RAHAYU PRIMA Village.